MENINGKATKAN KETERAMPILAN BERBICARA MELALUI METODE BERMAIN PERAN PADA ANAKUSIA 5-6 TAHUN - Niken Farida; Rahmi Wardah Ningsih; Ekawati Ekawati (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini (PGPAUD), 2022)
This study aims to improve the speaking skills of children in group B through the Role Playing method in OneRoof State Kindergarten 01 Hamparan Perak. This type of research is Classroom Action Research (CAR).The subjects of this study were children aged 5-6 years in class B, totaling 13 people, consisting of 7girls and 6 boys. The object of this research is an effort to improve speaking skills through role playing. Data collection techniques in this study were observation, documentation, and performance/ability (performance test). This research was conducted in two cycles consisting of 4 meetings. Data analysis techniques using percentages. After doing cycles I and II, it was found that there was an increase in the speaking skills of children aged 5-6 years. So it can be concluded that role playing can improve the speaking skills of childrenin group B aged 5-6 years in Satu Atap O1 Kindergarten, Hamparan Perak